Promoting speaking proficiency and willingness to communicate in Turkish young learners of English through asynchronous computer-mediated practice. (April 2017) - Buckingham, Louisa; Alpaslan, Rosie Stott
Abstract: This study investigated whether the provision of out-of-class speaking practice to young learners of English could contribute to improving speaking proficiency grades, and have a positive impact on children's willingness to communicate. Two intact classes of Grade 3 Turkish learners participated. Recorded communicative exercises provided asynchronous speaking practice homework with the classroom teacher as the children's interlocutor, while the control group received traditional paper-based exercises. The content of materials used in both groups was based on the class syllabus. A comparison of the speaking test scores of the control and experimental groups revealed that, over a four-month period, the use of the interactive recordings contributed to a significant improvement in the children's assessed oral performance. The implementation was particularly successful in raising the speaking test scores of children who had initially received lower scores. A subsequent ANOVA analysis revealed that the experimental group demonstrated an improvement in their ability to respond confidently with minimal pauses and hesitations, although the length of responses did not change significantly. The integration of such computer-mediated activities for homework speaking practice is potentially particularly useful in contexts where parents lack sufficient English skills to support children with their English-language homework tasks.